Lan Na literature : catalogue of 954 secular titles among the 3,700 palm-leaf manuscripts borrowed from wats throughout northern Thailand and preserved on microfilm at the Social Research Institute of Chiang Mai University - Chiang Mai University. Social Research Institute (Bangkok, 1986)
1 v. (unpaged)